Existência e multiplicidade de soluções positivas para uma classe de problemas elíticos - Dias, Francisco Helmuth Soares (2014)
The aim of this work is to give some sufficient conditions for the existence and multiplicity of the solutions for a class of elliptic problems, using for this variational methods, such as Montain Pass Theorem and the Ekeland Variational Principle.